Hand Recognition Obtained by Simulation of Hand Regard - Homma, Takahiro (Frontiers in Psychology, 2018)
Eye-hand coordination of an infant is observed during the early months of their development. Hand regard, which is an example of this coordination, occurs at about two months. It is considered that after experiencing hand regard, an infant may recognize their own hands. However, it is unknown how an infant recognizes their hands through hand regard. Accordingly, the process by which an infant recognizes their hands and distinguishes between their hands and other objects was simulated. A simple neural network was trained with a modified real-time recurrent learning (RTRL) algorithm to deal with time-varying input and output during hand regard. The simulation results show that information about recognition of the modeled hands of an infant is stored in cell assemblies, which were self-organized. Cell assemblies appear during the phase of U-shaped developments of hand regard, and the configuration of the cell assemblies changes with each U-shaped development. Furthermore, movements like general movements appear during the phase of U-shaped developments of hand regard.